Bacterial Contamination Test Using (TPC) Method on Traditional Herbal Medicine Kunyit Asam and Beras Kencur In Tugu Mulyo Village, South Sumatra - Saiful Saiful Anwar; Riong Seulina Panjaitan (Jurnal FARMASIMED (JFM), 2025)
Background: Traditional herbal medicine (jamu) is part of Indonesia’s cultural heritage and is still widely consumed for its health benefits. However, its safety is often threatened by microbiological contamination caused by unhygienic production processes. An important parameter to assess safety is the Total Plate Count (TPC), also known as Angka Lempeng Total (ALT). Methods: This study applied purposive sampling by collecting jamu kunyit asam and beras kencur samples from three producers in Tugu Mulyo Village, South Sumatra. TPC testing was performed using the pour plate method on Nutrient Agar, incubated for 24 hours at 37°C, followed by colony counting and expressed as CFU/mL. Gram staining was used to identify bacterial characteristics. Results: The TPC values of jamu kunyit asam were 1.0×10⁴ CFU/mL (sample 1), 3.9×10⁴ (sample 2), and 4.8×10⁴ (sample 3). The TPC values of jamu beras kencur were 5.4×10⁴ (sample 1), 1.0×10⁴ (sample 2), and 6.4×10⁴ (sample 3). All results were below the maximum limit set by BPOM (≤5.0×10⁷ CFU/mL). Gram staining revealed purple rod-shaped isolates, categorized as Gram-positive and identified as Bacillus sp. Conclusion: Jamu kunyit asam and beras kencur from Tugu Mulyo Village meet microbiological safety standards and are safe for consumption.